Strategies and applications of Islamic entrepreneurship - Rafiki, Ahmad 1981-; Pananjung, AlFatih Gessan; Nasution, Muhammad Dharma Tuah Putra 1974- (Advances in Logistics, Operations, and Management Science (ALOMS), 2023)
"As many countries are now looking for alternative ways of doing business with a focus on preserving ethics, morals, and values, it is important to understand and consider Islamic business. Islamic business, management, and entrepreneurship are topics that are discussed by many scholars; however, researchers in some countries have yet to comprehensively understand and implement current models, strategies, and applications. Strategies and applications of Islamic entrepreneurship considers all aspects of Islamic business, management, and entrepreneurship. The book also provides the best practices and challenges of implementing Islamic business models. Covering key topics such as Islamic marketing, Islamic business environments, and Muslim countries, this premier reference source is ideal for managers, business owners, policymakers, industry professionals, researchers, academicians, scholars, instructors, and students."--